Phytochemistry, bioactivities and future prospects of mulberry leaves: A review. (15th March 2022) - Ma, Guangqun; Chai, Xiaoyun; Hou, Guige; Zhao, Fenglan; Meng, Qingguo
Highlights: Mulberry leaves have a wide range of traditional and potential new health food uses. Mulberry leaves are almost maximized and have high economic value. Phenolic constituents play an important role in edible and medicinal value. The evidence is largely based on in vitro and in vivo studies of varying quality. It is necessary to further study the possible anticancer uses of mulberry leaves. Abstract: Mulberry leaves (MLs) have been used traditionally to raise silkworms and as herbs and herbal drinks. In vitro and in vivo studies as well as some clinical trials provide some evidence of health benefits, mostly for ML extracts. ML extracts showed antioxidant, hypoglycemic, anticholesterol (affecting lipid metabolism), antiobesity, anti-inflammatory, anticancer activities, and so on. These might be linked to strong antioxidant activities, inhibition of α -glucosidase and α -amylase, reduction of foam cell formation, inhibition of fat formation, decrease of NF-κB activity, and the promotion or induction of apoptosis. Phenolic constituents, especially flavonoids, phenolic acids and alkaloids, are likely to contribute to the reported effects. The phytochemistry and pharmacology of MLs confer the traditional and current uses as medicine, food, fodder, and cosmetics. This paper reviews the economic value, chemical composition and pharmacology of MLs to provide a reference for the development and utilization of MLs.